A Systematic Approach towards Synthesis and Design of Pervaporation‐Assisted Separation Processes1. Issue 11 (19th September 2017) - Scharzec, Bettina; Waltermann, Thomas; Skiborowski, Mirko
Abstract: While membrane processes like pervaporation are considered as key technology towards more sustainable separation processes, they are rarely considered in conceptual design. In order to enable an identification of promising applications, the current article proposes a systematic approach that covers the synthesis of pervaporation‐assisted process variants and promotes the use of optimization‐based methods for process analysis. It seeks to minimize and guide necessary experiments and includes competitive reference processes as well as further means for process intensification in the evaluation. Abstract : Although pervaporation is one of the most mature membrane processes, it is rarely considered in conceptual design. The current article presents a systematic approach for the identification of promising applications of pervaporation‐assisted separation processes, including further means of process intensification.